PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN KOPERASI SIMPAN PINJAM RAPDOS JAYA OKU SELATAN - Sela Suswani; Rosmala Dewi; Dyah Ayu Putriani (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2024)
This study aimed to determine the influence of workload and work stress on turnover intention among employees of Rapdos Jaya Savings and Loan Cooperative, south OKU. The data collection technique in this study was conducted through the distribution of questionnaires to a population of 32 people. The analysis technique used was multiple linear regression. Based on the partial analysis results, there was an influence of the workload variable on turnover intention among employees of Rapdos Jaya Cooperative with a t-count value of 9.991 > t-table value of 2.045, and there was an influence of the work stress variable on turnover intention among employees of Rapdos Jaya Savings and Loan Cooperative, south OKU with a t-count value of 2.674 > t-table value of 2.045. Simultaneously, it was found that there was an influence of workload and work stress on turnover intention among employees of Rapdos Jaya Savings and Loan Cooperative, south OKU with an F-count value of 63.619 > F-table value of 3.33. The determination coefficient (R²) obtained was 0.814, indicating that the contribution of the influence of workload and work stress on turnover intention among employees of Rapdos Jaya Savings and Loan Cooperative, south OKU was 81.4%, while the remaining 18.6% was influenced by other variables not mentioned in this study, such as perceived organizational support, organizational commitment, and other factors (Riani et al. 2017).